The Concept of Time: A Multiple Reference Reading - Chekatt, Hassiba; Boussehaba, Sabrina (Journal of Ecohumanism, 2026)
This study presents a multiple reference reading of the concept of time in its transformation across an evolutionary path, accompanied by a clear transformation in human thinking and in the ways of understanding what surrounds themzThe debate has intensified over the existence of time or its non-existence, and over its nature and formation as a necessary human need. The concept of time is reconsidered each time as a problematic issue whose presence is multiple and whose philosophical, linguistic, critical, and creative references are also multiple.Given the importance of time as an active element in human life and in discourse, its concept has transformed and varied, moving from simplicity to complexity with the increasing complexity of the issues of reality and life.